A one-year teacher professional development programme towards context-based science education using a concerns-based approach. Issue 3 (27th May 2022) - de Putter - Smits, Lesley G.A.; Nieveen, Nienke M; Taconis, Ruurd; Jochems, Wim
ABSTRACT: Professional development programmes for teachers that aim at context-based science education are usually lengthy and less effective than intended. In this study, a one-year professional development programme was designed and evaluated that consistently started from the teachers' concerns regarding context-based education. The teachers reported a positive shift in concerns, from self-as-teacher concerns towards student-learning concerns. They also reported that they came to grips with what context-based science education means in teaching practice. Although the number of participants was small (n = 5), this study uncovers that focusing on teachers' concerns throughout the professional development programme is a potentially effective approach to teacher learning. The shifts in their concerns is an important condition for long-lasting change.